2000
DOI: 10.1023/a:1007155525020
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The immediate-early cyclooxygenase-2 (COX-2) gene encodes an inducible prostaglandin synthase enzyme which is implicated in inflammatory and proliferative diseases. COX-2 is highly induced during cell activation by various factors, including mitogens, hormones and cytokines. Since pro-inflammatory cytokine IL-1beta has been shown to induce prostaglandin E2 (PGE2) release in human gingival fibroblasts (HGF), here we analyzed the effect of IL-1beta on the expression of COX-2 and the activation of NFkappaB in HGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Since the induction of COX-2 is frequently regulated by NF-kB (Nakao et al, 2000;Lim et al, 2001;Surh et al, 2001), we attempted to examine the effects of [6]gingerol on TPA-stimulated DNA binding and transcriptional activity of NF-kB in mouse skin. For this Figure 2 Inhibitory effects of [6]-gingerol on phorbol esterinduced COX-2 expression in mouse skin.…”
Section: Resultsmentioning
confidence: 99%
“…Since the induction of COX-2 is frequently regulated by NF-kB (Nakao et al, 2000;Lim et al, 2001;Surh et al, 2001), we attempted to examine the effects of [6]gingerol on TPA-stimulated DNA binding and transcriptional activity of NF-kB in mouse skin. For this Figure 2 Inhibitory effects of [6]-gingerol on phorbol esterinduced COX-2 expression in mouse skin.…”
Section: Resultsmentioning
confidence: 99%
“…U0126 (5 M) was used to inhibit MAP kinase kinase activity (52). Sodium orthovanadate (50 M) and okadaic acid (50 nM) were used for tyrosine phosphatase and serine-threonine phosphatase inhibition, respectively (53,54). Forskolin (1 M) was used for activation of adenylate cyclase (45).…”
Section: Experimrntal Proceduresmentioning
confidence: 99%
“…Previous results indicate that Cot kinase increases interleukin-2 gene expression (14 -16) mainly by up-regulating the transcription driven by NF-B and the composite element NFAT-AP-1 of interleukin-2 promoter (16); Cot kinase also up-regulates the AP-1 response element of the collagenase promoter (12,14,16). It has been shown that COX-2 promoter contains binding sites for these transcription factors, acting as positive regulatory elements of COX-2 transcription in several cell types (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). However, we have shown here that activation of COX-2 promoter in T cells occurs in a NF-kB-independent manner, in agreement with previous results discarding a role of this transcription factor in this cell type.…”
Section: Involvement Of the Calcineurin/nfat Pathway In The Activatiomentioning
confidence: 99%
“…This induction takes place at the transcriptional level and is mediated by two NFAT sites in the COX-2 promoter (21). Previous studies in different cells types (including vascular endothelial cells, lung epithelial cells, synoviocytes, pancreatic cells, gingival fibroblasts, and monocytes) have shown the importance of NF-B and AP-1 transcription factors in other cell types (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%